2016
DOI: 10.1080/10538712.2015.1108944
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Child Sexual Abuse in the Nordic Countries: A Literature Review

Abstract: This review examined child sexual abuse in the Nordic countries focusing on prevalence rates and victims' age and relationship to the perpetrator. The results show a prevalence of child sexual abuse (broadly defined) between 3-23% for boys and 11-36% for girls. The prevalence rates for contact abuse were 1-12% for boys and 6-30% for girls, while 0.3-6.8% of the boys and 1.1-13.5% of the girls reported penetrating abuse. The findings suggest an increased risk of abuse from early adolescence. In adolescence, pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
41
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 41 publications
10
41
0
9
Order By: Relevance
“…The participants reported that the perpetrator of the abuse was a relative in 8% of the instances of coercive touching and in 4% of instances of coercive sex (Table ). Although our estimates are in line with past studies (Finkelhor, Shattuck, Turner, & Hamby, ; Kloppen, Haugland, Svedin, Maehle, & Breivik, ), we might underestimate the prevalence of intrafamilial sexual abuse. As the participants were asked about sexual victimization when they are 18 years old, it is probable that most of them still live with their parents, which might have decreased their willingness to disclose such information.…”
Section: Discussionsupporting
confidence: 88%
“…The participants reported that the perpetrator of the abuse was a relative in 8% of the instances of coercive touching and in 4% of instances of coercive sex (Table ). Although our estimates are in line with past studies (Finkelhor, Shattuck, Turner, & Hamby, ; Kloppen, Haugland, Svedin, Maehle, & Breivik, ), we might underestimate the prevalence of intrafamilial sexual abuse. As the participants were asked about sexual victimization when they are 18 years old, it is probable that most of them still live with their parents, which might have decreased their willingness to disclose such information.…”
Section: Discussionsupporting
confidence: 88%
“…In a Nordic literature review, including 26 studies between 1990 and 2014, the prevalence of child sexual abuse (broadly defined) was found to vary between 3–23% for girls and 11–36% boys. The prevalence rates for contact abuse were 6–30% for girls and 1–12% for boys, while 1.1–13.5% of the girls and 0.3–6.8% of the boys reported penetrating abuse 1. A recurrent Swedish report “Young, sex and internet in a changing world” have, for example, with the use of the same question, found that self-reported penetrative abuse experiences ranged between 9.2–13.5% among women and 3.0–5.5% among men aged 18 years (http://www.allmannabarnhuset.se).…”
Section: Introductionmentioning
confidence: 94%
“…Sexual abuse includes rape, other forms of contact abuse and non-contact abuse, and occurs worldwide 1 2. In a meta-analysis of 331 international studies it was shown that an overall estimated prevalence of self-reported child sexual abuse to be 12.7% (girls 18.0% and boys 7.6%) 2.…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual age difference is not clearly defined and this has been identified as a gap in current research knowledge (May‐Chahal et al, ). An arbitrary five‐year difference has been adopted by some professionals and is referred to in some of the literature (Kloppen et al, ; May‐Chahal et al, ). Other authors exploring socio‐demographic characteristics of CSA victims and their abusers have used a range of different age cut‐offs (Darroch et al, ; Hendriks and Bijleveld, ), or quote mean ages and age ranges for the victim and his/her abuser (Kucuk, ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, rather than refer to actual ages, the term ‘child’ is used to represent the victim and ‘adult’ for the perpetrator (Berelowitz et al, ; Leclerc et al, ; May‐Chahal et al, ). Or the perpetrator is referred to in terms of his/her relationship to the victim such as father, mother, sibling, friend of the family or babysitter, from which the reader may infer that the perpetrator is older (Bahali et al, ; Hendriks and Bijleveld, ; Kloppen et al, ; Kucuk, ).…”
Section: Introductionmentioning
confidence: 99%